EAR1 Negatively Regulates ABA Signaling by Enhancing 2C Protein Phosphatase Activity. Issue 4 (4th April 2018) - Wang, Kai; He, Junna; Zhao, Yang; Wu, Ting; Zhou, Xiaofeng; Ding, Yanglin; Kong, Lingyao; Wang, Xiaoji; Wang, Yu; Li, Jigang; Song, Chun-Peng; Wang, Baoshan; et al.
Abstract : EAR1 is a general negative regulator that interacts with the N termini of clade A type 2C protein phosphatases, releases their autoinhibition, and enhances their activity during ABA signaling. Abstract: The reversible phosphorylation of proteins by kinases and phosphatases is an antagonistic process that modulates many cellular functions. Protein phosphatases are usually negatively regulated by inhibitor proteins. During abscisic acid (ABA) signaling, these inhibitor proteins comprise PYR1/PYL/RCAR ABA receptors, which inhibit the core negative regulators, the clade A type 2C protein phosphatases (PP2Cs). However, it is not known whether these PP2Cs are positively regulated by other proteins. Here, we identified an Arabidopsis thaliana ear1 ( enhancer of aba co-receptor1 ) mutant that exhibits pleiotropic ABA-hypersensitive phenotypes. EAR1 encodes an uncharacterized protein that is conserved in both monocots and dicots. EAR1 interacts with the N-terminal inhibition domains of all six PP2Cs, ABA INSENSITIVE1 (ABI1), ABI2, HYPERSENSITIVE TO ABA1 (HAB1), HAB2, ABA-HYPERSENSITIVE GERMINATION1 (AHG1), and AHG3, during ABA signaling and enhances the activity of PP2Cs both in vitro and in vivo. ABA treatment caused EAR1 to accumulate in the nucleus. These results indicate that EAR1 is a negative regulator of ABA signaling that enhances the activity of PP2Cs by interacting with and releasing the N-terminal autoinhibition of these proteins.